Design of Neutron Activation and Radiography Facilities Based on DD Generator - Prastowo, Dian Adi (Indonesian Journal of Physics, 2023)
Design and simulation of radiation facility using deuterium-deuterium (DD) neutron generator for neutron activation analysis (NAA) and radiography have been conducted by PHITS 3.30. A cylindrical DD neutron tube (E = 2.45 MeV isotropic, 5 x 109/s) flux is surrounded by high-density polyethylene blocks which serve as the moderator. Within the moderator there are several cavities to perform neutron activation experiments. A 90 cm long beam tube is installed either radially or tangentially for radiography purposes. Monte Carlo simulations then calculate the thermal flux inside the cavities and on the end of the beam tube. The biggest thermal flux obtained in the activation chambers is about 1.95 x 109/(cm2.s) in the cavity closest to the source center. Radial beam tube delivers thermal flux of 7.86 x 103/(cm2.s), while tangential beam tube transports 1.86 x 103/(cm2.s). Although the thermal flux in the radial beam tube is higher, the fast neutron flux is also higher, about 9.60 x 103/(cm2.s). Tangential beam tube configuration can decrease fast neutron flux to only 2.00 x 102/(cm2.s). This result can serve as a preliminary study for the commisioning of radiation facilities based on compact, low-power neutron source.